2007
DOI: 10.1186/1750-9378-2-2
|View full text |Cite
|
Sign up to set email alerts
|

The co-evolved Helicobacter pylori and gastric cancer: trinity of bacterial virulence, host susceptibility and lifestyle

Abstract: Helicobacter pylori is an important yet unproven etiological agent of gastric cancer. H. pylori infection is more prevalent in developing Asian countries like India and it is usually acquired at an early age. It has been two decades since Marshall and Warren (1984) first described curved bacilli in the stomach of ulcer and gastritis patients. This discovery has won them the Nobel Prize recently, but the debate whether H. pylori is a pathogen or a commensal organism is still hot. Associations with disease-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…It seems that the infection by H. pylori can be related to socioeconomic status which in turn effects on papulation’s lifestyle. The outcomes of clinical manifestations of this bacterium are influenced by three factors, severity of strains, host genetics, and environment [ 56 ]. Reciprocally and over the time the stomach status such as acidity, buffering and mucus content can be affected by lifestyle factors such as diet, food habits, alcoholism, oral hygiene, water hygiene, personal hygiene, and so on [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the infection by H. pylori can be related to socioeconomic status which in turn effects on papulation’s lifestyle. The outcomes of clinical manifestations of this bacterium are influenced by three factors, severity of strains, host genetics, and environment [ 56 ]. Reciprocally and over the time the stomach status such as acidity, buffering and mucus content can be affected by lifestyle factors such as diet, food habits, alcoholism, oral hygiene, water hygiene, personal hygiene, and so on [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori , a bacterium initially observed in 1893 ( [14] cited in [15] ), has not been recognized as an infectious agent until 1982—in the seminal work of Nobel Laureates, Warren and Marshall [16–18] . H. pylori colonizes various regions of the upper digestive system, mainly the stomach and duodenum, causing stomach and duodenal ulcers and certain stomach cancers [9,19,20] . The infection is surprisingly common, and the bacteria are believed to colonize more than half of the world’s population [21] .…”
Section: Helicobacter Pylori and Its Transmissionmentioning
confidence: 99%
“…Thus, it was concluded that targeting these potentially virulent factors would stop the disease establishment and would enable a rapid development of novel vaccines, antibiotics and new screening tests. The three main approaches that have been used for the identification of virulence genes from the complete genome involves: homology search with the experimentally characterized virulent factors ( Rana et al, 2015c ), identifying genes located in different pathogenic genomic islands ( Akhter et al, 2007 , 2008 , 2012 ; Che et al, 2014 ) and the third approach involves identification of the virulence genes by genome comparison of strains having different pathogenicity profiles (virulent versus avirulent strains). Using an in silico approach, a set of 189 putative vaccine candidates have been identified from the complete Mtb genome (3989 gene products) ( Zvi et al, 2008 ).…”
Section: Application Of Proteome-scale In Silico Smentioning
confidence: 99%